THE SPANISH ARTISTIC HERITAGE IN 1939: DOES CHANGE OF DIRECTION IN THE REPUBLICAN CULTURAL POLICY? (Tzintzun, Revista de Estudios Históricos, 2016)
The Spanish Civil War represented a turning point in the Western world, withregard to the traditional methods and techniques used by Museum curators toprotect and preserve the Artistic Heritage. The Republic governments started up,between 1936 and 1939, a detailed project to save the Spanish heritage. This projectwas a response to the high importance that culture had for Republican elites.During the last months of the Civil War, contradictions developing the projectemerged leading to important controversies that are nowadays still unsolved. Theseproblems incited the dispersion as well as the destruction of an important part ofthe Artistic Heritage, which had been kept safe during the conflict. The works of artin question were part of the cargo that the yacht Vita shipped to Mexico.
Keywords: Artistic Heritage; Culture; Black market in art; Second Republic; Spanish Civil War